1999
DOI: 10.1149/1.1392627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Film Stress on the Chemical Mechanical Polishing Process

Abstract: A theoretical model is constructed to simulate the pressure distribution arising from wafer curvature (film stress) during chemical mechanical polishing (CMP), based on theories of elastic contact stress. Results from oxide CMP experiments suggest that the wafer curvature results in a nonuniform polish rate distribution across the wafer, in agreement with the simulation based on the model. This stress-dependent polish nonuniformity is attributed to the nonuniform pressure distribution across the wafer, induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 14 publications
0
22
0
1
Order By: Relevance
“…In this experiment, pressure effects on material removal profile were considered. Tseng et al (1999) simulated the pressure distribution at the wafer level during CMP. Their results revealed that the pressures at the wafer edge are larger than those at the wafer center, and the pressure-high edge profile determines the MRR profile.…”
Section: Pressurementioning
confidence: 99%
“…In this experiment, pressure effects on material removal profile were considered. Tseng et al (1999) simulated the pressure distribution at the wafer level during CMP. Their results revealed that the pressures at the wafer edge are larger than those at the wafer center, and the pressure-high edge profile determines the MRR profile.…”
Section: Pressurementioning
confidence: 99%
“…These values were incorporated into Eq. (8) to obtain the wafer's nonuniformity, R, which equals to 5.33. However, the simulated c and max from the CMP model with a retaining ring were 5 80 * 10 −2 MPa and 1 76 * 10 −1 MPa, respectively.…”
Section: Wafer's Nonuniformitymentioning
confidence: 99%
“…The profile of the stress distribution is similar to that in Wang et al [6], but the site of peak stress is somewhat different. Tseng et al [8] constructed a theoretical model based on Hertzian contact theory to simulate the pressure distribution along the pad/wafer interface arising from wafer curvature during the CMP process. They found that the film stress does not bring about a significant change in removal rate, but it induces a redistribution of pressure profile.…”
Section: Introductionmentioning
confidence: 99%
“…Модель химико-механического полирования и концепция молекулярного воздействия абразивных частиц суспензии на поверхность полируемой поверхности с учетом окисляю-щей способности компонентов и образования тонких оксидных пленок рассмотрена в [17][18][19]. В связи с этим развивается теория молекулярно-атомного воздействия абразивного материала на полируемую поверхность [20,21].…”
Section: Introductionunclassified